Dependence of Thyroid Sonographic Markers of Malignancy and Its Influence on the Diagnostic Value of Sonographic Findings. (22nd January 2015) - Woliński, Kosma; Stangierski, Adam; Szczepanek-Parulska, Ewelina; Gurgul, Edyta; Ruchała, Marek
Abstract : Introduction . Thyroid nodules constitute frequent medical condition. Ultrasonographic (US) examination remains the basis in the diagnostics of nodular goiter and selection of the suspected ones requiring fine-needle aspiration biopsy (FNAB). The aim of this study was to evaluate if the features so far considered to be US malignancy markers are dependent or independent variables and to check if these data are clinically relevant. Materials and Methods . Patients with diagnosed thyroid nodular goiter admitted for thyroidectomy, irrespectively of the indications for surgery, were involved. The following parameters were assessed: echogenicity, the presence of calcifications, presence of halo, shape, margins, structure (solid, partially or pure cystic), and elasticity of the nodules (assessed quantitatively). Results . 122 consecutive patients with 393 thyroid nodules were included. There were significant associations between halo absence and irregular borders, micro- and macrocalcifications, taller-than-wide feature and macrocalcifications, irregular margins and macrocalcifications, and also decreased elasticity of nodules and several attributes (partially cystic character, micro- and macrocalcifications). Conclusions . Not only diagnostic value of particular sonographic features but also data about cooccurrence and associations between them are clinically relevant. Although most of these features turned out to be independent, omitting significant association can lead to incorrect assessment of the risk of malignancy.